Norbornene and Related Structures as Scaffolds in the Search for New Cancer Treatments - Gorka Calvo-Martín; Daniel Plano; Nuria Martínez-Sáez; Carlos Aydillo; Esther Moreno; Socorro Espuelas; Carmen Sanmartín (MDPI AG, 2022)
The norbornene scaffold has arisen as a promising structure in medicinal chemistry due to its possible therapeutic application in cancer treatment. The development of norbornene-based derivatives as potential chemotherapeutic agents is attracting significant attention. Here, we report an unprecedented review on the recent advances of investigations into the antitumoral efficacy of different compounds, including the abovementioned bicyclic scaffold in their structure, in combination with chemotherapeutic agents or forming metal complexes. The impact that structural modifications to these bicyclic compounds have on the antitumoral properties and the mechanisms by which these norbornene derivatives act are discussed in this review. In addition, the use of norbornene, and its related compounds, encapsulation in nanosystems for its use in cancer therapies is here detailed.